Behavior of the black flying fox, Pteropus alecto (Chiroptera: Pteropodidae) in cages - TILTJE ANDRETHA RANSALELEH; INDYAH WAHYUNI; MARTHA KAWATU; MEIS JACINTA NANGOY; SIGIT WIANTORO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ransaleleh TA, Wahyuni I, Kawatu M, Nangoy MJ, Wiantoro S. 2021. Behavior of the black flying fox, Pteropus alecto (Chiroptera: Pteropodidae) in cages. Biodiversitas 22: 5657-5665. Hunting and illegal trading have become a common thread for the black flying fox in Sulawesi, Indonesia. However, information on its biology and behavior as a baseline for conservation and management program is still lacking. Therefore, this study aims to examine the behavioral activities of black flying fox, Pteropus alecto (Temminck, 1837) kept in cages through direct observation. The results showed that feeding was carried out by descending to the bottom of the cage before picking up fruits with the mouth and wings. Furthermore, the time associated with this process ranged from 06.01 to 10.00, while agonistic behavior performed using claws and wings took place from 10.01 to 14.00 in the daytime and 22.01 to 02.00 at night. Grooming was carried out using the tongue and wings, from 14.01 to 18.00 during the day and 22.01 to 02.00 during the night. Subsequently, the bats slept by perching with the eyes closed and the whole body wrapped with the wings from 02.01 to 10.00, while locomotion and stationary behaviors were performed by perching with eyes open and flying around the cage with the wings spread apart from 10.01 to 14.00 during the day and 22.01 to 02.00 at night. The percentage of day and night behavior activities consist of agonistic 0.12%, grooming 6.14%, eating 19.36%, sleeping 56.33%, and stationary and locomotive 17.76%. The results improve the understanding of P. alecto's daily activities in the cage which are difficult to observe in the wild and provide insight for conservation and wildlife management. Furthermore, information from this study is useful for future bat captivity programs.